(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Wildlife tourism is one of the important components of tourism around the world. Kerala, better known as “God’s own Country” which is a federal state of India is one of the sought after tourism destinations for tourists across the world. Wildlife tourism is the upcoming sector of tourism development as far as Kerala tourism is concerned. When the visitors get positive experience, they are likely to revisit or recommend the destination to others. So it is very important to identify the factors underlying the experience of visitor management in wildlife tourism areas. In this paper, the researchers developed a scale to examine the core factors contributing to the experience of visitors on visitor management. The study found that the factors contributing to visitor management experiences are Experience on Directorial Information, Experience on Modification of the Site, Experience on Management related Information, Experience on Interpretive information, Experience on Site Personnel, Experience on Ticket Counter and Experience on Destination Vehicle.